Short-b-axis hydrogen type ZSM-5 molecular sieve, preparation method thereof, catalytic cracking catalyst and application thereof

CN122940182APending Publication Date: 2026-10-20CHINA NAT PETROLEUM CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510462105.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-14
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

但是,这种设计的模板剂通常比较昂贵,不利于工业化的生产

Benefits of technology

[0045](1)本发明提供的短b轴氢型ZSM-5分子筛的制备方法,当所述初始混合物含有晶种时,通过晶种诱导法,无需自制特殊的晶种,直接选择市售的ZSM-5分子筛作为晶种,未经过任何的处理,无需添加任何有机模板剂,通过引入晶面生长添加剂、采用两段温度晶化的方法,即可得到具有结晶度高、b轴尺寸短、介孔体积和外比表面积高、分子扩散性能优异的ZSM-5分子筛。此外,所使用的添加剂不含氟离子、尿素等不利于废水处理和环境保护的材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005359321470000011
    Figure HDA0005359321470000011
  • Figure HDA0005359321470000012
    Figure HDA0005359321470000012
  • Figure HDA0005359321470000021
    Figure HDA0005359321470000021
Patent Text Reader

Abstract

This invention provides a short b-axis hydrogen-type ZSM-5 molecular sieve, its preparation method, catalytic cracking catalyst, and its application. The preparation method includes: mixing a silicon source, an aluminum source, an alkali source, and water; first stirring to obtain an initial mixture; adding an additive to the initial mixture; second stirring to obtain an initial gel; subjecting the initial gel to two-stage temperature crystallization; washing, drying, and a first calcination to obtain molecular sieve powder; subjecting the molecular sieve powder to ion exchange, washing, drying, and a second calcination to obtain a short b-axis hydrogen-type ZSM-5 molecular sieve; the initial mixture also contains seed crystals or an organic template agent. When seed crystals are present, this invention employs a seed-induced method, eliminating the need for any organic template agent. By introducing additives and using a two-stage temperature crystallization method, a ZSM-5 molecular sieve with high crystallinity, a short b-axis size, and excellent molecular diffusion performance can be obtained; and it can be used to prepare a catalytic cracking catalyst with high crude oil conversion and high diene yield.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalytic materials, specifically relating to a short b-axis hydrogen-type ZSM-5 molecular sieve and its preparation method, catalytic cracking catalyst and its application. Background Technology

[0002] The ZSM-5 molecular sieve framework contains two intersecting pore systems: zigzag channels (0.51 nm × 0.55 nm) along the ac plane and cylindrical ten-membered ring channels (0.53 nm × 0.56 nm) parallel to the b-axis. The intersection of these two vertically connected channels has a diameter of 0.9 nm. Due to its unique three-dimensional pore structure, selectable acid strength distribution, and thermal stability, the ZSM-5 zeolite molecular sieve has become one of the most important catalytic materials in the petroleum industry, such as in catalytic cracking (FCC), methanol-to-olefins (MTO), and methanol-to-propylene (MTP). It is also widely used in fine chemicals, environmental protection, and electrochemistry.

[0003] ZSM-5 molecular sieve, as a microporous molecular sieve, offers excellent shape selectivity in catalytic reactions due to its micropores. However, these micropores also restrict the diffusion of reactants and products, leading to rapid coking and side reactions. Overcoming this diffusion limitation is often achieved by shortening the diffusion path length, including constructing ultra-large micropores within zeolite crystals, introducing mesopores or macropores into zeolite crystals, and preparing nanocrystals. For example, Choi et al. designed a bifunctional quaternary ammonium salt surfactant that can simultaneously guide the formation of zeolite structures at both the mesopore and micropore length scales, resulting in MFI zeolite nanosheets with a thickness of only 2 nm. This corresponds to the b-axis size of a single MFI unit cell, significantly increasing the surface area of ​​the monolayer molecular sieve to 710 m². 2 ·g -1 (Nature, 2009, 461, 246; J Am Chem Soc, 2010, 132, 4169; ACS Catal, 2011, 901).

[0004] Subsequently, extensive research was conducted on the preparation of nanosheet-like ZSM-5 molecular sieves using specially structured guided templates. Many different quaternary ammonium salt surfactants were designed, including those with different hydrophilic ends, different chain lengths for hydrophobic ends, and smaller molecular templates. All of these methods yielded nanosheet-like molecular sieves with good catalytic performance and high hydrothermal stability. However, these designed templates are typically expensive, hindering industrial-scale production.

[0005] Diffusion limitations can be overcome by reducing the grain size to the nanoscale. However, the separation of nanoscale molecular sieves often requires centrifugation, which is not conducive to their industrial application. In addition, nanoscale molecular sieves may puncture the skin and cause harm to the human body.

[0006] CN117566753A reports a synthesis process for b-axis oriented sheet-like ZSM-5 molecular sieves with high hydrothermal stability. The process prepares sheet-like ZSM-5 molecular sieves with ultra-high hydrothermal stability in a one-pot method. However, the preparation process requires the participation of organic structure directing agents and fluoride ions, which is not conducive to wastewater treatment.

[0007] CN115490243A reports a method for preparing a short b-axis HZSM-5 molecular sieve, which produces a fluffy ZSM-5 molecular sieve with short b-axis characteristics. However, this method requires the prior preparation of Silicate-1 seed suspension and also requires filtration using a membrane filter press. The preparation process is complex and not suitable for practical production.

[0008] CN113184875A reports a method for preparing an all-silica short b-axis ZSM-5 zeolite molecular sieve. The prepared molecular sieve inhibits undesirable reactions, such as coking, due to the lack of aluminum-related acidic centers. However, this method requires the participation of an organic template agent and urea to regulate b-axis growth, which is environmentally unfriendly.

[0009] Furthermore, the aforementioned studies have largely focused on zeolite powders rather than macroscopic catalyst masses. In industrial applications, most practical zeolite catalysts must be shaped to meet necessary mechanical strength requirements. Therefore, excessively thin nanosheet molecular sieves and nanocrystals are not conducive to their application in actual production operations.

[0010] Ethylene and propylene are important basic raw materials in the petrochemical industry, with wide applications in production and daily life. With the development of downstream industries of propylene, the demand for propylene is increasing. Currently, facing the dual problems of overcapacity in oil refining and a shortage of propylene resources, the propylene yield and selectivity of catalytic cracking are insufficient to meet the requirements of refinery transformation and upgrading, necessitating improvements and innovations in FCC propylene enhancement technology. Adding additives to the main catalyst has a relatively small impact on the production process and facilitates flexible operation, making it an effective way to enhance propylene production in FCC. ZSM-5 molecular sieve is a key component of FCC propylene enhancement catalysts / additives.

[0011] Therefore, there is a need for a method to prepare short b-axis ZSM-5 molecular sieves that is simple, inexpensive, and does not require organic template agents with special structures, so as to further obtain catalytic cracking catalysts with high propylene yield and selectivity. Summary of the Invention

[0012] To address the aforementioned technical problems, the present invention aims to provide a short b-axis hydrogen-type ZSM-5 molecular sieve, its preparation method, catalytic cracking catalyst, and its application.

[0013] To achieve the above objectives, the present invention provides a method for preparing a short b-axis hydrogen-type ZSM-5 molecular sieve, wherein the preparation method includes:

[0014] Step 1: Mix silicon source, aluminum source, alkali source and water, and obtain an initial mixture after the first stirring; wherein, based on SiO2, Al2O3, Na2O and H2O, the molar ratio of silicon source, aluminum source, alkali source and water is (20-200):1:(0.5-6.5):(550-1200);

[0015] Step 2: Add the additive to the initial mixture and stir for a second time to obtain the initial gel; wherein the molar ratio of the additive to the aluminum source is (0.15-5):1;

[0016] Step 3: The initial gel is subjected to two-stage temperature crystallization, followed by washing, drying, and a first calcination to obtain molecular sieve powder;

[0017] Step 4: The molecular sieve raw powder undergoes ion exchange, washing, drying, and a second calcination to obtain short b-axis hydrogen-type ZSM-5 molecular sieve;

[0018] The initial mixture further contains seed crystals or an organic template agent, wherein:

[0019] When seed crystals are present, the amount of seed crystals added is 0.35 wt% to 2.5 wt%, based on the total mass of silicon source, aluminum source, alkali source and water as 100%.

[0020] When an organic template agent is present, the molar ratio of the organic template agent to the aluminum source is (0-2.5):1, wherein the aluminum source is calculated as Al2O3.

[0021] According to a specific embodiment of the present invention, preferably, the additive includes one or a combination of two or more of ammonia, ammonium carbonate, ammonium sulfate, ammonium chloride, and ammonium bicarbonate; more preferably, it is ammonia and / or ammonium carbonate. In the present invention, the additive, as a crystal facet growth inhibitor, can selectively adsorb onto the

[010] crystal facet of the molecular sieve, thereby inhibiting the growth of the molecular sieve along the b-axis direction. Ammonia is an aqueous solution, which is beneficial for better dispersion in the gel and is inexpensive; furthermore, the ammonium ions provided by ammonia can act as both a mineralizing agent and adsorb onto specific crystal faces to control the b-axis size of the molecular sieve; while ammonium carbonate, as an inorganic substance, is easily soluble in water, inexpensive, and environmentally friendly.

[0022] According to a specific embodiment of the present invention, preferably, the silicon source includes one or more of coarse-pore silica gel, tetraethyl silicate, silica sol, and water glass.

[0023] According to a specific embodiment of the present invention, preferably, the aluminum source includes one or a combination of two or more of aluminum sulfate, boehmite, sodium aluminate, and aluminum hydroxide.

[0024] According to a specific embodiment of the present invention, preferably, the seed crystals include one or a combination of two or more of Silicate-1 molecular sieve, hydrogen-form ZSM-5 molecular sieve, and Silicate-1 seed crystal suspension; more preferably, the seed crystals are hydrogen-form ZSM-5 molecular sieve. When the initial mixture contains seed crystals, the present invention uses a seed-induction method to replace expensive template agents, and commercially available conventional ZSM-5 molecular sieve seed crystals can be used directly without special self-made processes.

[0025] In some specific embodiments, preferably, the alkali source is sodium hydroxide.

[0026] In some specific implementations, preferably, the molar ratio of the silicon source, aluminum source, alkali source, and water, based on SiO2, Al2O3, Na2O, and H2O, is (20-45):1:(0.5-3.5):(700-1200). Appropriately reducing the amount of alkali added is beneficial to reducing the grain size, thereby shortening the b-axis dimension.

[0027] According to a specific embodiment of the present invention, preferably, in the two-stage temperature crystallization, the temperature of the first stage crystallization is 100-150℃, and the crystallization time is 6-48 hours; the temperature of the second stage crystallization is 150-200℃, and the crystallization time is 6-72 hours; more preferably, the temperature of the first stage crystallization is 110-130℃, and the crystallization time is 16-24 hours; the temperature of the second stage crystallization is 170-190℃, and the crystallization time is 26-48 hours. In the present invention, the two-stage temperature crystallization is mainly used to generate more crystal nuclei to reduce the size of the molecular sieve crystals, thereby shortening the b-axis dimension and reducing the thickness of the molecular sieve. At the first crystallization temperature, the additives can be uniformly dispersed in the synthesis system, which is beneficial for their adsorption on specific crystal faces, thereby suppressing the thickness of the molecular sieve b-axis. Appropriately extending the processing time of the first stage crystallization is beneficial for reducing the crystal size, thereby shortening the b-axis dimension.

[0028] In some specific embodiments, preferably, the temperature of the first stirring is 25-95°C and the stirring time is 2-30 hours; more preferably, the temperature of the first stirring is 30-60°C and the stirring time is 10-24 hours.

[0029] In some specific implementations, preferably, the temperature of the second stirring is the same as that of the first stirring, and the second stirring time is 0.5-12 hours.

[0030] In some specific embodiments, preferably, when the initial mixture contains seed crystals, the operation of mixing raw materials in step one is as follows: first, mix the seed crystals, alkali source, aluminum source, and water, and perform a first stirring; then, add the silicon source and continue the first stirring to obtain the initial mixture; or, first, mix the water and silicon source, and perform a first stirring; then, add the alkali source and seed crystals, and continue the first stirring; finally, dissolve the aluminum source in water and add it to the synthesis system, and after a first stirring, obtain the initial mixture. When mixing the water and silicon source first, the first stirring can be performed at a lower temperature (e.g., 30-50°C), and after adding the alkali source, seed crystals, and aluminum source, the temperature can be appropriately increased to perform the first stirring at a higher temperature (e.g., 50-80°C), so that the raw materials are dissolved more fully, which is beneficial to obtaining a well-crystallized molecular sieve.

[0031] In some specific implementations, preferably, in step three, the drying conditions are drying at 60-120°C overnight, more preferably drying at 80-120°C for 8-16 hours.

[0032] In some specific implementations, preferably, in step four, the drying conditions are drying at 60-120°C overnight, more preferably drying at 80-120°C for 8-16 hours.

[0033] In some specific implementations, preferably, the temperature of the first roasting is 350-650°C, and the roasting time is 2-8 hours.

[0034] In some specific implementations, preferably, the second roasting temperature is 350-650°C and the second roasting time is 2-8 hours.

[0035] In this invention, when the initial mixture contains seed crystals, the synthesis of molecular sieves with short b-axis characteristics can be achieved without any organic template agent (e.g., without a special-function bis-quaternary ammonium salt organic template agent or a conventional organic template agent). Furthermore, the method of inhibiting b-axis growth by introducing additives is applicable not only to seed-induced methods without adding any organic template agents, but also to systems that synthesize molecular sieves using ordinary conventional organic template agents. That is, when the initial mixture contains organic template agents, molecular sieves with short b-axis characteristics can also be obtained.

[0036] According to a specific embodiment of the present invention, preferably, the organic template agent includes one or a combination of two or more of tetraethylammonium bromide, tetrapropylammonium bromide, tetrabutylammonium bromide, tetrapropylammonium hydroxide, ethylamine, and butylamine. In this invention, when the initial mixture contains an organic template agent, there is no need to synthesize additional special organic template agents (e.g., bis-quaternary ammonium salt organic template agents with special functions); conventional organic template agents can be used synergistically with additives to obtain molecular sieves with short b-axis characteristics.

[0037] The present invention also provides a short b-axis hydrogen-type ZSM-5 molecular sieve, which is prepared by the above preparation method.

[0038] According to a specific embodiment of the present invention, preferably, the b-axis size of the short b-axis hydrogen-type ZSM-5 molecular sieve is 30-170 nm, and the average b-axis size is below 91 nm; the proportion of b-axis sizes below 100 nm is more than 65%; more preferably, the b-axis size is 30-120 nm, and the average b-axis size is 55 nm-91 nm; even more preferably, the b-axis size is 30-90 nm, the average b-axis size is 55 nm-65 nm, and the proportion of b-axis sizes below 80 nm is more than 80%.

[0039] In some specific embodiments, preferably, the silica-to-alumina ratio of the short b-axis hydrogen-type ZSM-5 molecular sieve is not higher than 38. When the silica-to-alumina ratio is low, the prior art often inevitably leads to an increase in the b-axis thickness due to more aluminum entering the molecular sieve. In contrast, the present invention overcomes the problem of the prior art's inability to simultaneously achieve a low silica-to-alumina ratio and a short b-axis by introducing additives into the synthesis system.

[0040] The present invention also provides a catalytic cracking catalyst, wherein, by mass percentage, the raw materials of the catalytic cracking catalyst include 35 wt% molecular sieve, 45 wt%-55 wt% kaolin and 10 wt%-20 wt% binder;

[0041] The molecular sieve, based on the total mass of the raw materials as 100%, consists of 5wt%-10wt% of the aforementioned short b-axis hydrogen-type ZSM-5 molecular sieve and 25wt%-30wt% of USY molecular sieve.

[0042] In some specific embodiments, preferably, the catalytic cracking catalyst is prepared by mixing molecular sieves with kaolin and a binder, pulping the mixture, and then spray molding it.

[0043] This invention also provides the application of the above-mentioned catalytic cracking catalyst in the catalytic cracking reaction of feedstock oil, especially in the field of heavy oil catalytic cracking technology in the petroleum refining industry.

[0044] Existing conventional methods for synthesizing short b-axis ZSM-5 molecular sieves often require the addition of expensive and difficult-to-obtain template agents, which is detrimental to subsequent separation and large-scale industrial experiments. Compared with existing technologies, the advantages of this invention are:

[0045] (1) The method for preparing short b-axis hydrogen-type ZSM-5 molecular sieve provided by this invention, when the initial mixture contains seed crystals, uses a seed-induced method. Without the need for self-made special seed crystals, commercially available ZSM-5 molecular sieves are directly selected as seed crystals. No treatment is required, and no organic template agent is added. By introducing crystal growth additives and employing a two-stage temperature crystallization method, ZSM-5 molecular sieves with high crystallinity, short b-axis size, high mesopore volume and external specific surface area, and excellent molecular diffusion performance can be obtained. Furthermore, the additives used do not contain fluoride ions, urea, or other materials detrimental to wastewater treatment and environmental protection.

[0046] (2) The method for preparing short b-axis hydrogen-type ZSM-5 molecular sieve provided by the present invention, when the initial mixture contains an organic template agent, does not require the additional synthesis of a special organic template agent. With the help of additives and two-stage temperature crystallization, ZSM-5 molecular sieve with high crystallinity, short b-axis size, high mesopore volume and external specific surface area, and excellent molecular diffusion performance can be obtained.

[0047] (3) The catalytic cracking catalyst provided by the present invention, by using short b-axis hydrogen-type ZSM-5 molecular sieve as an additive, not only achieves high crude oil conversion rate, but also improves propylene yield and diene yield, and has great application prospects in the petrochemical field.

[0048] (4) In the existing methods for synthesizing ZSM-5 molecular sieves, in order to pursue a shorter b-axis, ZSM-5 molecular sieves often inevitably have a high silicon-to-aluminum ratio. However, the short b-axis ZSM-5 molecular sieve obtained by this invention can maintain a low silicon-to-aluminum ratio, achieving the characteristics of both a short b-axis and a low silicon-to-aluminum ratio. This provides a basis for controlling the silicon-to-aluminum ratio of the molecular sieve framework to achieve the control of acid density. Attached Figure Description

[0049] Figure 1 This is a schematic diagram of ZSM-5 molecular sieve crystals.

[0050] Figure 2 The XRD patterns of the samples prepared in Examples 1-5 are shown.

[0051] Figure 3 The XRD patterns of the samples prepared for comparative examples 1-2 are shown.

[0052] Figure 4 SEM image and b-axis size statistics of the short b-axis hydrogen-type ZSM-5 molecular sieve prepared in Example 1.

[0053] Figure 5 SEM image and b-axis size statistics of the short b-axis hydrogen-type ZSM-5 molecular sieve prepared in Example 2.

[0054] Figure 6 SEM image and b-axis size statistics of the short b-axis hydrogen-type ZSM-5 molecular sieve prepared in Example 3.

[0055] Figure 7 SEM image and b-axis size statistics of the short b-axis hydrogen-type ZSM-5 molecular sieve prepared in Example 4.

[0056] Figure 8 SEM image and b-axis size statistics of the short b-axis hydrogen-type ZSM-5 molecular sieve prepared in Example 5.

[0057] Figure 9 SEM image of the hydrogen-form ZSM-5 molecular sieve prepared for Comparative Example 1.

[0058] Figure 10 SEM images and b-axis dimension statistics of the hydrogen-form ZSM-5 molecular sieve prepared for Comparative Example 2.

[0059] Figure 11 The nitrogen adsorption-desorption isotherms are for the samples prepared in Examples 1-2 and Comparative Example 1. Detailed Implementation

[0060] In order to provide a clearer understanding of the technical features, objectives and beneficial effects of the present invention, the technical solution of the present invention will now be described in detail below, but it should not be construed as limiting the scope of implementation of the present invention.

[0061] Example 1

[0062] This embodiment provides a method for preparing short b-axis hydrogen-type ZSM-5 molecular sieves, the specific steps of which are as follows:

[0063] Step 1: Weigh 5g of seed crystals (commercially available H-ZSM-5 molecular sieve), 15.5g of sodium hydroxide (96wt%), 20.8g of aluminum sulfate, and 322g of water into a beaker. Stir at 50℃ until the mixture is homogeneous, controlling the speed at 300r / min. Then slowly add 248g of alkaline silica sol (30wt% silica content) and continue stirring for 10 hours to obtain the initial mixture.

[0064] Step 2: Weigh 5.5g of ammonia water and add it to the initial mixture. Stir for 2 hours while controlling the speed at 400r / min to obtain the initial gel.

[0065] Step 3: Transfer the initial gel to an autoclave and place the autoclave in a rotary oven to allow the initial gel to undergo two-stage temperature crystallization. The first stage of crystallization is carried out at 120°C for 16 hours, and the second stage is carried out at 180°C for 26 hours. After the crystallization is completed and the autoclave is cooled to room temperature, the slurry is removed, washed with deionized water, and filtered until neutral. Then, it is placed in an oven and dried at 80°C for 12 hours. After a first calcination at 550°C for 4 hours, the molecular sieve powder is obtained.

[0066] Step 4: The molecular sieve raw powder is subjected to ion exchange twice in 1M NH4Cl solution at 90℃ for 2 hours. After washing until neutral, it is dried in an oven at 120℃ for 12 hours and then calcined at 550℃ for 4 hours to obtain short b-axis hydrogen-type ZSM-5 molecular sieve. The amount of NH4Cl solution used is 1g of molecular sieve per 100mL of NH4Cl solution.

[0067] A schematic diagram of the crystallite of the short b-axis hydrogen-type ZSM-5 molecular sieve prepared in this embodiment is shown below. Figure 1 As shown, by Figure 1 As can be seen, the b-axis refers to the grain thickness (L). b A shorter b-axis indicates that the molecular sieve crystals are thinner.

[0068] The XRD pattern of the short b-axis hydrogen-type ZSM-5 molecular sieve prepared in this embodiment is shown below. Figure 2 As shown, by Figure 2 It can be seen that the relative crystallinity is 88%, and the characteristic diffraction peaks of the MFI topology appear at 2θ of 7.96°, 8.83°, 23.18°, 23.99° and 24.45°, and there are no diffraction peaks of other impurities.

[0069] The scanning electron microscope image and b-axis thickness statistical diagram of the short b-axis hydrogen-type ZSM-5 molecular sieve prepared in this embodiment are shown below. Figure 4 As shown, by Figure 4 It can be seen that the prepared molecular sieve is relatively thin and has a short b-axis. The average value of the b-axis is 63 nm, with about 96% of the b-axis being below 100 nm and about 83% being below 80 nm. Furthermore, about 8% of the b-axis dimensions are below 40 nm.

[0070] Example 2

[0071] This embodiment provides a method for preparing short b-axis hydrogen-type ZSM-5 molecular sieve. The specific steps are basically the same as those in Example 1, except that ammonia is replaced with 7g of ammonium carbonate, while the other parameters and steps remain unchanged.

[0072] The XRD pattern of the short b-axis hydrogen-type ZSM-5 molecular sieve prepared in this embodiment is shown below. Figure 2 As shown, by Figure 2It can be seen that the relative crystallinity is 90%, and the characteristic diffraction peaks of the MFI topology appear at 2θ of 7.96°, 8.83°, 23.18°, 23.99° and 24.45°, and there are no diffraction peaks of other impurities.

[0073] The scanning electron microscope image and b-axis thickness statistical diagram of the short b-axis hydrogen-type ZSM-5 molecular sieve prepared in this embodiment are shown below. Figure 5 As shown, by Figure 5 It can be seen that the prepared molecular sieve is relatively thin and has a short b-axis. The average value of the b-axis is 58 nm, with about 100% of the b-axis being below 100 nm, about 86% being below 70 nm, and about 10% of the b-axis dimensions being below 40 nm.

[0074] Example 3

[0075] This embodiment provides a method for preparing short b-axis hydrogen-type ZSM-5 molecular sieves, which uses different crystallization conditions and basicity compared to Example 2. The specific steps are as follows:

[0076] Step 1: Weigh 5g of seed crystals (commercially available H-ZSM-5 molecular sieve), 18.5g of sodium hydroxide (96wt%), 20.8g of aluminum sulfate, and 322g of water into a beaker. Stir at 50℃ until the mixture is homogeneous, controlling the speed at 300r / min. Then slowly add 248g of alkaline silica sol (30wt% silica content) and continue stirring for 10 hours to obtain the initial mixture.

[0077] Step 2: Weigh 7g of ammonium carbonate and add it to the initial mixture. Stir for 2 hours while controlling the speed at 400r / min to obtain the initial gel.

[0078] Step 3: Transfer the initial gel to an autoclave and place the autoclave in a rotary oven to allow the initial gel to undergo two-stage temperature crystallization. The first stage of crystallization is carried out at 120°C for 8 hours, and the second stage is carried out at 180°C for 8 hours. After the crystallization is completed and the autoclave is cooled to room temperature, the slurry is removed, washed with deionized water, and filtered until neutral. Then, it is placed in an oven and dried at 100°C for 12 hours. After a first calcination at 550°C for 4 hours, the molecular sieve powder is obtained.

[0079] Step 4: The molecular sieve raw powder is subjected to ion exchange twice in 1M NH4Cl solution at 90℃ for 2 hours. After washing until neutral, it is dried in an oven at 120℃ for 12 hours and then calcined at 550℃ for 4 hours to obtain short b-axis hydrogen-type ZSM-5 molecular sieve. The amount of NH4Cl solution used is 1g of molecular sieve per 100mL of NH4Cl solution.

[0080] The XRD pattern of the short b-axis hydrogen-type ZSM-5 molecular sieve prepared in this embodiment is shown below. Figure 2 As shown, by Figure 2 It can be seen that the relative crystallinity is 95%, and the characteristic diffraction peaks of the MFI topology appear at 2θ of 7.96°, 8.83°, 23.18°, 23.99° and 24.45°, and there are no diffraction peaks of other impurities.

[0081] The scanning electron microscope image and b-axis thickness statistical diagram of the short b-axis hydrogen-type ZSM-5 molecular sieve prepared in this embodiment are shown below. Figure 6 As shown, by Figure 6 It can be seen that the prepared molecular sieve is relatively thin and has a short b-axis. The average value of the b-axis is 90 nm, with about 65% of the b-axis being below 100 nm and about 88% being below 120 nm. Furthermore, about 13% of the b-axis dimensions are below 60 nm.

[0082] Example 4

[0083] This embodiment provides a method for preparing short b-axis hydrogen-type ZSM-5 molecular sieves, adjusting the amount of raw materials and basicity in the synthesis system. The specific steps are as follows:

[0084] Step 1: While continuously stirring at a speed of 300 r / min, weigh 279.2 g of deionized water and 80 g of coarse-porous silica gel (93 wt% silica content) into a beaker and mix thoroughly at 30 °C. Then weigh 20.8 g of NaOH (96 wt% content) and 5 g of seed crystals (commercially available H-ZSM-5 molecular sieve) and add them to the synthesis system, mixing at 50 °C for 30 min. Finally, weigh 20.8 g of aluminum sulfate, dissolve it in 50 g of deionized water, and add it to the synthesis system. Continue mixing at 50 °C for 24 hours to obtain the initial mixture.

[0085] Step 2: Weigh 7g of ammonium carbonate and add it to the initial mixture. Stir for 2 hours while controlling the speed at 400r / min to obtain the initial gel.

[0086] Step 3: Transfer the initial mixture to an autoclave and place the autoclave in an oven to allow the initial mixture to undergo two-stage temperature crystallization. The first stage of crystallization is carried out at 110°C for 24 hours, and the second stage is carried out at 190°C for 12 hours. After the crystallization is completed and the autoclave is cooled to room temperature, the slurry is removed, washed with deionized water, and filtered until neutral. It is then placed in an oven and dried at 120°C for 12 hours. After that, it is calcined in a muffle furnace at 550°C for 6 hours to obtain molecular sieve powder.

[0087] Step 4: The molecular sieve raw powder is subjected to ion exchange twice in 1M NH4Cl solution at 90℃ for 2 hours. After washing until neutral, it is dried in an oven at 120℃ for 12 hours and then calcined at 550℃ for 4 hours to obtain short b-axis hydrogen-type ZSM-5 molecular sieve. The amount of NH4Cl solution used is 1g of molecular sieve per 100mL of NH4Cl solution.

[0088] The XRD pattern of the short b-axis hydrogen-type ZSM-5 molecular sieve prepared in this embodiment is shown below. Figure 2 As shown, by Figure 2 It can be seen that the relative crystallinity is 97%, and the characteristic diffraction peaks of the MFI topology appear at 2θ of 7.96°, 8.83°, 23.18°, 23.99° and 24.45°, and there are no diffraction peaks of other impurities.

[0089] The scanning electron microscope image and b-axis thickness statistical diagram of the short b-axis hydrogen-type ZSM-5 molecular sieve prepared in this embodiment are shown below. Figure 7 As shown, by Figure 7 It can be seen that the prepared molecular sieve is relatively thin and has a short b-axis. The average value of the b-axis is 91 nm, with about 72% of the b-axis being below 100 nm and about 84% being below 120 nm. Furthermore, about 14% of the b-axis dimensions are below 60 nm.

[0090] Example 5

[0091] This embodiment provides a method for preparing hydrogen-form ZSM-5 molecular sieves, which involves adding conventional organic template agents along with additives. The specific steps are as follows:

[0092] Step 1: Under continuous stirring at a speed of 300 r / min, weigh 329.2 g of deionized water and 80 g of coarse-porous silica gel (93 wt% silica content) into a beaker and mix thoroughly at 50 °C. Then weigh 4.65 g of NaOH (96 wt%) and 17.05 g of organic template agent TPABr (tetrapropylammonium bromide) into the synthesis system and continue mixing at 50 °C for 30 min. Finally, weigh 4.8 g of pseudoboehmite into the synthesis system and mix at 80 °C for 12 hours to obtain the initial mixture.

[0093] Step 2: Weigh 8g of ammonium carbonate and add it to the initial mixture. Stir for 4 hours while controlling the speed at 350r / min to obtain the initial gel.

[0094] Step 3: Transfer the initial mixture to an autoclave and place the autoclave in an oven to allow the initial mixture to undergo two-stage temperature crystallization. The first stage of crystallization is carried out at 120°C for 16 hours, and the second stage is carried out at 180°C for 26 hours. After the crystallization is completed and the autoclave is cooled to room temperature, the slurry is removed, washed with deionized water, and filtered until neutral. It is then placed in an oven and dried at 120°C for 12 hours. After that, it is calcined in a muffle furnace at 550°C for 4 hours to obtain molecular sieve powder.

[0095] Step 4: The molecular sieve powder is subjected to ion exchange twice in 1M NH4Cl solution at 90℃ for 2 hours. After washing until neutral, it is dried in an oven at 120℃ for 12 hours and then calcined at 550℃ for 4 hours to obtain hydrogen-form ZSM-5 molecular sieve. The amount of NH4Cl solution used is 1g of molecular sieve for every 100mL of NH4Cl solution.

[0096] The XRD pattern of the hydrogen-form ZSM-5 molecular sieve prepared in this embodiment is shown below. Figure 2 As shown, by Figure 2 It can be seen that the relative crystallinity is 92%, and the characteristic diffraction peaks of the MFI topology appear at 2θ of 7.96°, 8.83°, 23.18°, 23.99° and 24.45°, and there are no diffraction peaks of other impurities.

[0097] The scanning electron microscope image and b-axis thickness graph of the hydrogen-form ZSM-5 molecular sieve prepared in this embodiment are shown below. Figure 8 As shown, by Figure 8 As can be seen, the average value of the b-axis is 80nm, with approximately 75% below 100nm and approximately 91% below 120nm.

[0098] Comparative Example 1

[0099] This comparative example provides a method for preparing hydrogen-form ZSM-5 molecular sieve. The specific steps are basically the same as in Example 1, except that no additives are introduced, while the other raw material ratios and experimental conditions are the same. The specific steps are as follows:

[0100] Step 1: Weigh 5g of seed crystals (commercially available H-ZSM-5 molecular sieve), 18.5g of sodium hydroxide (96wt%), 20.8g of aluminum sulfate, and 322g of water into a beaker. Stir at 50℃ until the mixture is homogeneous, controlling the speed at 250r / min. Then slowly add 248g of alkaline silica sol (30wt% silica content) and continue stirring for 12 hours to obtain the initial mixture.

[0101] Step 2: Transfer the initial mixture to an autoclave and place the autoclave in an oven to allow the initial mixture to undergo two-stage temperature crystallization. The first stage of crystallization is carried out at 120°C for 16 hours, and the second stage is carried out at 180°C for 26 hours. After the crystallization is completed and the autoclave is cooled to room temperature, the slurry is removed, washed with deionized water, and filtered until neutral. Then, it is placed in an oven and dried at 100°C for 12 hours. After a first calcination at 550°C for 4 hours, molecular sieve powder is obtained.

[0102] Step 3: The molecular sieve powder is subjected to two ion exchanges in 1M NH4Cl solution at 90℃ for 2 hours. After washing until neutral, it is dried in an oven at 120℃ for 12 hours and then calcined at 550℃ for 4 hours to obtain hydrogen-form ZSM-5 molecular sieve. The amount of NH4Cl solution used is 1g of molecular sieve for every 100mL of NH4Cl solution.

[0103] The XRD pattern of the hydrogen-form ZSM-5 molecular sieve prepared in this comparative example is shown below. Figure 3 As shown, by Figure 3 It can be seen that the relative crystallinity is 95%, and the characteristic diffraction peaks of the MFI topology appear at 2θ of 7.96°, 8.83°, 23.18°, 23.99° and 24.45°, and there are no diffraction peaks of other impurities.

[0104] The scanning electron microscope image of the hydrogen-form ZSM-5 molecular sieve prepared in this comparative example is shown below. Figure 9 As shown, by Figure 9 It is evident that the ZSM-5 molecular sieves agglomerate and stack together, failing to yield hydrogen-type ZSM-5 molecular sieves with a distinct b-axis orientation. This indicates that short b-axis ZSM-5 molecular sieves cannot be obtained without the introduction of additives.

[0105] Comparative Example 2

[0106] This comparative example provides a method for preparing hydrogen-form ZSM-5 molecular sieves, employing single-stage temperature crystallization conditions. The specific steps are as follows:

[0107] Step 1: Weigh 5g of seed crystals (commercially available H-ZSM-5 molecular sieve), 15.5g of sodium hydroxide (96wt%), 20.8g of aluminum sulfate, and 322g of water into a beaker. Stir at 50℃ until the mixture is homogeneous, controlling the speed at 250r / min. Then slowly add 248g of alkaline silica sol (silica content 30wt%) and continue stirring for 22h to obtain the initial mixture.

[0108] Step 2: Weigh 8g of ammonium carbonate and add it to the initial mixture. Stir for 2 hours while controlling the speed at 350r / min to obtain the initial gel.

[0109] Step 3: Transfer the initial gel to an autoclave and place the autoclave in a rotary oven to allow the initial gel to undergo single-stage temperature crystallization. The crystallization conditions are 180°C for 24 hours. After the crystallization is completed and the autoclave is cooled to room temperature, the slurry is removed, washed with deionized water, and filtered until neutral. It is then placed in an oven and dried at 100°C for 12 hours. After a first calcination at 550°C for 4 hours, molecular sieve powder is obtained.

[0110] Step 4: The molecular sieve powder is subjected to ion exchange twice in 1M NH4Cl solution at 90℃ for 2 hours. After washing until neutral, it is dried in an oven at 120℃ for 12 hours and then calcined at 550℃ for 4 hours to obtain hydrogen-form ZSM-5 molecular sieve. The amount of NH4Cl solution used is 1g of molecular sieve for every 100mL of NH4Cl solution.

[0111] The XRD pattern of the hydrogen-form ZSM-5 molecular sieve prepared in this comparative example is shown below. Figure 3 As shown, by Figure 3 It can be seen that the relative crystallinity is 93%, and the characteristic diffraction peaks of the MFI topology appear at 2θ of 7.96°, 8.83°, 23.18°, 23.99° and 24.45°, and there are no diffraction peaks of other impurities.

[0112] Scanning electron microscope images and b-axis thickness statistics of the hydrogen-form ZSM-5 molecular sieve prepared in this comparative example. Figure 10 As shown, by Figure 10 It can be seen that the average value of the b-axis is 101 nm, which is higher than that of other embodiments, and the overall size distribution is relatively wide. Only about 58% of the size is below 100 nm, and about 20% of the b-axis size exceeds 120 nm, and about 4% exceeds 170 nm. This indicates that single-segment temperature crystallization is not conducive to obtaining hydrogen-type ZSM-5 molecular sieves with concentrated b-axis size distribution and short b-axis size.

[0113] Test Example 1

[0114] The physicochemical properties of the hydrogen-form ZSM-5 molecular sieves prepared in Examples 1-2 and Comparative Example 1 were tested and evaluated, and the results are as follows:

[0115] The nitrogen adsorption-desorption isotherms and pore structure properties of the hydrogen-form ZSM-5 molecular sieve are shown in the figure. Figure 11 See Table 1.

[0116] Table 1. Texture properties of the samples

[0117] Sample number <![CDATA[S BET m 2 / g]]> <![CDATA[S Micro m 2 / g]]> <![CDATA[S External m 2 / g]]> <![CDATA[V Total cm 3 / g]]> <![CDATA[V Micro cm 3 / g]]> <![CDATA[V Meso cm 3 / g]]> Example 1 365 276 89 0.198 0.135 0.063 Example 2 353 256 97 0.205 0.119 0.086 Comparative Example 1 385 308 77 0.182 0.135 0.047 Comparative Example 2 344 275 69 0.219 0.134 0.085

[0118] As shown in Table 1, the hydrogen-form ZSM-5 molecular sieves obtained in conventional Comparative Example 1 and the short b-axis hydrogen-form ZSM-5 molecular sieves synthesized in Examples 1-2 of this invention both have similar micropore volumes, indicating that both have high crystallinity and can be compared with... Figure 2 , Figure 3 The XRD patterns correspond to those in Comparative Example 1. However, compared to Comparative Example 1, Examples 1-2 have higher mesopore volume and external specific surface area (S). External The increased mesopore volume and external specific surface area facilitate diffusion and provide higher accessibility to active sites. Meanwhile, a comparison between Example 2 and Comparative Example 2 shows that although the mesopore volume of the sample prepared by single-stage temperature crystallization in Comparative Example 2 is close to that of Example 2, the specific surface area of ​​Comparative Example 2 is relatively small, and its external specific surface area is much lower than that of Example 2.

[0119] In addition, the elemental analysis of the hydrogen-type ZSM-5 molecular sieves prepared in Example 1 and Comparative Examples 1-2 is shown in Table 2.

[0120] Table 2. Elemental composition of the samples

[0121] Sample number Silicon-to-aluminum ratio (XRF) <![CDATA[w(SiO2)%]]> <![CDATA[w(Al2O3)%]]> <![CDATA[w(Na2O)%]]> Comparative Example 1 39 95.28 4.073 0.1 Example 1 37 95.39 4.32 0.1 Comparative Example 2 38 95.52 4.27 0.1

[0122] As shown in Table 2, combined with Figure 9 When the silicon-to-aluminum ratio of Comparative Example 1 is low, more aluminum enters the molecular sieve, leading to an increase in the b-axis size. In addition, the aggregation and stacking of the molecular sieve also increases the b-axis size. In contrast, this application can solve both of these problems at the same time by introducing additives into the synthesis system. This allows Example 1 to reduce the b-axis size while maintaining a low silicon-to-aluminum ratio, resulting in a hydrogen-type ZSM-5 molecular sieve with both a low silicon-to-aluminum ratio and a short b-axis. This further provides a basis for controlling the acid density by regulating the silicon-to-aluminum ratio of the molecular sieve framework.

[0123] Preparation Example 1

[0124] This preparation example provides a catalytic cracking catalyst, and the specific preparation steps are as follows:

[0125] The short b-axis hydrogen-type ZSM-5 molecular sieve prepared in Example 1 was mixed with an appropriate amount of kaolin and binder, slurried, and spray-dried. The mixing ratio of the raw materials by mass percentage was as follows: 35 wt% molecular sieve (5 wt% ZSM-5 molecular sieve + 30 wt% commercially purchased USY molecular sieve), 50 wt% matrix kaolin and 15 wt% alumina sol binder. The above raw materials were slurried and mixed evenly, and then spray-dried to obtain catalyst microspheres.

[0126] The catalyst microspheres were aged at 800°C with 100% steam for 4 hours, and the resulting catalyst was named Cat-1 and used to evaluate the device.

[0127] Preparation Example 2

[0128] This preparation example provides a catalytic cracking catalyst, and the specific preparation steps are as follows:

[0129] The hydrogen-form ZSM-5 molecular sieve obtained in Comparative Example 1 was mixed with an appropriate amount of kaolin and binder, slurried, and spray-dried. The mixing ratio of the raw materials by mass percentage was as follows: 35 wt% molecular sieve (5 wt% ZSM-5 molecular sieve + 30 wt% commercially purchased USY molecular sieve), 50 wt% matrix kaolin and 15 wt% alumina sol binder. The above raw materials were slurried and mixed evenly, and then spray-dried to obtain catalyst microspheres.

[0130] The catalyst microspheres were aged at 800℃ with 100% steam for 4 hours, and the resulting catalyst was named Cat-2 and used to evaluate the device.

[0131] Preparation Example 3

[0132] This preparation example provides a catalytic cracking catalyst, and the specific preparation steps are as follows:

[0133] The hydrogen-type ZSM-5 molecular sieve obtained in Comparative Example 2 was mixed with an appropriate amount of kaolin and binder, slurried, and spray-dried. The mixing ratio of the raw materials by mass percentage was as follows: 35 wt% molecular sieve (5 wt% ZSM-5 molecular sieve + 30 wt% commercially purchased USY molecular sieve), 50 wt% matrix kaolin and 15 wt% alumina sol binder. The above raw materials were slurried and mixed evenly, and then spray-dried to obtain catalyst microspheres.

[0134] The catalyst microspheres were aged at 800°C with 100% steam for 4 hours, and the resulting catalyst was named Cat-3 and used to evaluate the device.

[0135] Test Example 2

[0136] The catalytic performance of the catalysts in Preparation Examples 1-2 was evaluated using the ACE fixed fluidized bed evaluation device (Kayser). The results are as follows:

[0137] Experimental conditions: catalyst loading was 9 grams, oil feed rate was 1.5 grams, oil feed time was 75 seconds, catalyst-to-oil ratio was 6.0, and reaction temperature was 530℃. The feedstock used was an industrial catalytic cracking unit feedstock with a density (20℃) of 0.86 g / cm³. 3 The freezing point is 34℃, the residual carbon is 3.07wt%, and the Ni content is 3.27μg / g.

[0138] The gaseous products generated during the experiment were analyzed by online refinery gas chromatography, and the liquid products were analyzed by simulated distillation chromatography to determine the gasoline and diesel fraction content. The catalyst carbon deposits were regenerated online, and the carbon deposit content was obtained using a CO2 analyzer. The product distribution and cracked gas distribution of different catalysts used in the cracking reaction in Preparation Examples 1-2 are shown in Tables 3 and 4.

[0139] Table 3. Product distribution of heavy oil catalytic cracking reaction

[0140] project Cat-1 (%) Cat-2 (%) Cat-3 (%) dry air 2.54 2.32 2.43 Liquefied gas 17.40 13.22 15.66 gasoline 53.52 58.77 55.36 Light circulation oil 9.04 7.83 8.55 Oil slurry 8.78 8.39 8.72 coke 8.72 9.47 9.28 Conversion rate 82.18 83.78 82.73

[0141] Note: Conversion rate = 100% - percentage content of slurry oil - percentage content of light circulating oil

[0142] Table 4. Distribution of cracked gas from the cracking reaction

[0143] project Cat-1 (%) Cat-2 (%) Cat-3 (%) hydrogen 0.17 0.18 0.17 methane 0.73 0.66 0.67 Ethane 0.54 0.52 0.53 ethylene 1.10 0.97 1.06 propane 0.68 0.52 0.57 propylene 7.83 6.12 6.95 n-Butane 0.35 0.26 0.32 Isobutane 0.69 0.36 0.61 C4 olefins 7.85 5.95 7.21 Ethylene + Propylene 8.93 7.09 8.01

[0144] According to the reaction evaluation data in Tables 3 and 4, under the same reaction conditions, all three catalysts exhibited crude oil conversion efficiencies of over 80%, indicating that crude oil underwent significant cracking under the action of the catalysts.

[0145] Of particular note is that, when the silicon-to-aluminum ratio is similar, the catalyst (Cat-1) prepared from the short b-axis hydrogen-form ZSM-5 molecular sieve in Preparation Example 1, compared to the catalyst (Cat-2) prepared from the conventional hydrogen-form ZSM-5 molecular sieve in Preparation Example 2, showed a 1.71% increase in propylene yield and a 1.84% increase in diene (ethylene + propylene) yield. This indicates that the low silicon-to-aluminum ratio, short b-axis hydrogen-form ZSM-5 molecular sieve provided by the present invention, when added as an additive to the catalyst, can effectively improve the propylene yield. Furthermore, although the catalyst (Cat-3) prepared from the molecular sieve obtained by single-stage temperature crystallization showed increased propylene and diene (ethylene + propylene) yields compared to Cat-2, its catalytic performance was still inferior to that of Cat-1.

[0146] In the petrochemical processing field, the base capacity of catalytic cracking is enormous, so even a slight change in yield, even a fraction of a percent, can result in substantial overall benefits; this also proves that short b-axis hydrogen-type ZSM-5 molecular sieves have great application prospects in the petrochemical field.

Claims

1. A method for preparing short b-axis hydrogen-type ZSM-5 molecular sieve, wherein, The preparation method includes: Step 1: Mix silicon source, aluminum source, alkali source and water, and obtain an initial mixture after the first stirring; wherein, based on SiO2, Al2O3, Na2O and H2O, the molar ratio of silicon source, aluminum source, alkali source and water is (20-200):1:(0.5-6.5):(550-1200); Step 2: Add the additive to the initial mixture and stir for a second time to obtain the initial gel; wherein the molar ratio of the additive to the aluminum source is (0.15-5):1; Step 3: The initial gel is subjected to two-stage temperature crystallization, followed by washing, drying, and a first calcination to obtain molecular sieve powder; Step 4: The molecular sieve raw powder undergoes ion exchange, washing, drying, and a second calcination to obtain short b-axis hydrogen-type ZSM-5 molecular sieve; The initial mixture further contains seed crystals or an organic template agent, wherein: When seed crystals are present, the amount of seed crystals added is 0.35 wt% to 2.5 wt%, based on the total mass of silicon source, aluminum source, alkali source and water as 100%. When an organic template agent is present, the molar ratio of the organic template agent to the aluminum source is (0-2.5):1, wherein the aluminum source is calculated as Al2O3.

2. The preparation method according to claim 1, wherein, The additives include one or more of ammonia, ammonium carbonate, ammonium sulfate, ammonium chloride, and ammonium bicarbonate.

3. The preparation method according to claim 1, wherein, The silicon source includes one or more of the following: coarse-porous silica gel, tetraethyl silicate, silica sol, and water glass.

4. The preparation method according to claim 1, wherein, The aluminum source includes one or more of aluminum sulfate, boehmite, sodium aluminate, and aluminum hydroxide.

5. The preparation method according to claim 1, wherein, The seed crystals include one or a combination of two or more of Silicate-1 molecular sieve, hydrogen-type ZSM-5 molecular sieve, and Silicate-1 seed crystal suspension.

6. The preparation method according to claim 1, wherein, In the two-stage temperature crystallization, the temperature of the first stage crystallization is 100-150℃ and the crystallization time is 6-48 hours; the temperature of the second stage crystallization is 150-200℃ and the crystallization time is 6-72 hours.

7. The preparation method according to claim 1, wherein, The organic template agent includes one or more of tetraethylammonium bromide, tetrapropylammonium bromide, tetrabutylammonium bromide, tetrapropylammonium hydroxide, ethylamine, and butylamine.

8. A short b-axis hydrogen-type ZSM-5 molecular sieve, which is prepared by the preparation method according to any one of claims 1-7.

9. The short b-axis hydrogen-type ZSM-5 molecular sieve according to claim 8, wherein, The b-axis size of this short b-axis hydrogen-type ZSM-5 molecular sieve is 30-170 nm, and the average b-axis size is below 91 nm. More than 65% of the b-axis dimensions are below 100nm.

10. A catalytic cracking catalyst, wherein, The feedstock of the catalytic cracking catalyst comprises 35 wt% molecular sieve, 45 wt%-55 wt% kaolin and 10 wt%-20 wt% binder, by weight percentage. The molecular sieve, based on the total mass of the raw materials as 100%, consists of 5wt%-10wt% of the short b-axis hydrogen-type ZSM-5 molecular sieve as described in claim 8 or 9 and 25wt%-30wt% of the USY molecular sieve.

11. The application of the catalytic cracking catalyst according to claim 10 in the catalytic cracking reaction of feedstock oil.

Citation Information

Patent Citations

  • Preparation method of all-silicon short b-axis ZSM-5 zeolite molecular sieve

    CN113184875A

  • Flaky ZSM-5 molecular sieve with high hydrothermal stability and preparation method thereof

    CN117566753A